Multi-functional colloidal gels as cell bioinstructive platforms for tissue engineering - Gonçalves, Leandro dos Santos (2023)
Colloidal gels represent one of the most promising classes of biomaterials for biomedical applications owing to their potential for exploring different nanoparticle combinations towards the assembly of macro-scale multi-particle platforms. In these systems, nanosized units can serve both as crosslinking nodes and as structural building blocks resulting in highly hierarchic networks. Typically, these nanostructured systems leverage intrinsic supramolecular interactions for self-assembling. The resulting constructs present highly attractive physicochemical properties, such as viscoelasticity, self-healing and shear-thinning features and may present injectability and fit-to-shape features. Despite the inherent potential of colloidal gels, their exploitation as inks for additive manufacturing, namely 3D printing, is still limited and largely unexplored. In fact, most of the current developed colloidal systems are single-network assembled via weak particle-particle supramolecular interactions (such as Van der Waals, electrostatic, etc.), not providing sufficient mechanical stability to 3D printed constructs, which often exhibit a low structural lifetime. To overcome these limitations, this master dissertation focused on the development of a 3D-printable double-network colloidal ink with refined programable, modular and inherent cell supporting features. For this, two oppositely charged unitary nanoparticle building-blocks that also exhibited light-responsiveness were initially combined via electrostatic-driven bottom-up assembly, resulting in the formulation of a colloidal ink with suitable rheological properties to be processed via extrusion 3D printing. The presence of light-responsive chemical moieties in nanoparticles enabled the production of double network (i.e., electrostatic and covalent) constructs exhibiting mechanical robustness after light induced in situ photocrosslinking. The resulting constructs were biocompatible and exhibited adhesive properties for enabling human adipose derived mesenchymal stems adhesion, promoting cell spreading and proliferation, for more than 14 days. These findings support the future use of these systems as cell bioinstructive platforms and as highly modular and processable inks for 3D printing of nanoparticle only constructs that may find numerous biomedical applications.